ILLOCUTIONARY SPEECH ACTS IN THE SPEECH OF THE PRESIDENT OF THE REPUBLIC OF INDONESIA ON THE REPEAL OF PPKM: IN THE STUDY OF THE PHILOSOPHY OF LANGUAGE J. L. AUSTIN - Vitalia Hanako Murni Simanjuntak; Fernando De Napoli Marpaung; Edi Suprayetno (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This study’s goal is to figure out what kinds of illocutionary speech acts President Joko Widodo used when he talked about firing PPKM in Indonesia. After studying the philosophy of language, J.L. Austin’s theory on the speaking acts of language is used as a theoretical foundation. Qualitative or linguistic research methods are used in this method of study. In this research, the way information is gathered is by listening and taking notes. In this study, President Joko Widodo’s speech about firing PPKM in Indonesia, which includes illocutionary speech acts, is used as a source of data. This study is based on an address that Joko Widodo posted on Instagram about the end of PPKM in Indonesia. According to the research that has been done, President Joko Widodo talked about the firing of PPKM in Indonesia 22 times in his speech. With 9 utterances, illocutionary expositives made up most of the study’s findings. Exercitives came in second with 7 utterances, followed by commissive with 4 and behabilitives with 2.